-3(h+5)+2=4(h+6)

Simple and best practice solution for -3(h+5)+2=4(h+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(h+5)+2=4(h+6) equation:


Simplifying
-3(h + 5) + 2 = 4(h + 6)

Reorder the terms:
-3(5 + h) + 2 = 4(h + 6)
(5 * -3 + h * -3) + 2 = 4(h + 6)
(-15 + -3h) + 2 = 4(h + 6)

Reorder the terms:
-15 + 2 + -3h = 4(h + 6)

Combine like terms: -15 + 2 = -13
-13 + -3h = 4(h + 6)

Reorder the terms:
-13 + -3h = 4(6 + h)
-13 + -3h = (6 * 4 + h * 4)
-13 + -3h = (24 + 4h)

Solving
-13 + -3h = 24 + 4h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4h' to each side of the equation.
-13 + -3h + -4h = 24 + 4h + -4h

Combine like terms: -3h + -4h = -7h
-13 + -7h = 24 + 4h + -4h

Combine like terms: 4h + -4h = 0
-13 + -7h = 24 + 0
-13 + -7h = 24

Add '13' to each side of the equation.
-13 + 13 + -7h = 24 + 13

Combine like terms: -13 + 13 = 0
0 + -7h = 24 + 13
-7h = 24 + 13

Combine like terms: 24 + 13 = 37
-7h = 37

Divide each side by '-7'.
h = -5.285714286

Simplifying
h = -5.285714286

See similar equations:

| 4a-4a^2=0 | | -88-12X=7-2x-6 | | R+20=50 | | -x^4-2x^2+1=0 | | 11+4p=4+3p | | 5-9n+5n=27-82 | | 11Z-17=105 | | -2q-3q=18 | | 7x^2=104 | | log(2x-5)=1 | | 7+3d-5=-1+2-12+d | | 7+6x=4(x-5)+7 | | 2k^2-19k+10=0 | | 4t-t-5=2t-8 | | 15.4+3.5=-1.2h-6 | | 8(3b+3)=5b+5 | | 7s+2s-7s=8 | | -9x-6=4x+33 | | (5y+3)(2y+7)=11y-10 | | x^7-3x^6=0 | | Q+10=25 | | 4x-(9x+3)=7x-27 | | 4(c+1)=16 | | 6Z-5=37 | | .79x+230=43777 | | 16=80 | | 3x+15-6x=-(-x+1) | | [k-10]=30 | | 2(x-1)(x-5)=0 | | 16=480 | | 1.5d+5.25=3+2.25d | | 2x+35+5x-22= |

Equations solver categories